Role of endogenous nitric oxide in unilateral ureteropelvic junction obstruction in children - Garramuño, Patricia (2003)
Background. Obstructive nephropathy leads to tubulointerstitial fibrosis and loss of renal function. Nitric oxide has been shown to have antifibrotic properties. We examined nitric oxide synthase (NOS) activity and expression in kidneys from children who underwent surgery release of unilateral ureteropelvic junction (UPJ) obstruction in relation to clinical and histologic parameters. Methods. NOS activity and the expression of NOS isoforms measured at the mRNA level by reverse transcription-polymerase chain reaction (RT-PCR) assay were determined in tissue obtained by biopsy from obstructed kidneys of 18 children at the time of pyeloplasty. Tissue from kidneys removed because of various malignancies were issued as control. Results. A significant increase in calcium/calmodulin-independent NOS activity (iNOS) and iNOS mRNA expression was found in the medulla of obstructed kidneys. Calcium/ calmodulin-dependent NOS activity (cNOS) and endothelial (eNOS) mRNA, by contrast, were increased in the cortex from obstructed kidneys. A role of tumor necrosis factor-α (TNF-α) on enhanced iNOS was suggested by the finding of increased urine levels in obstructed pelvis. Increased interstitium macrophage number, by immunolabeling of CD68, was related to the delay in obstruction release and to decreased glomerular filtration rate (GFR) at surgery. A positive linear relationship was found between cNOS activity in cortex and creatinine clearance. The degree of interstitial fibrosis correlated negatively with cNOS activity in cortex. Conclusion. In kidneys from children with UPJ obstruction an increased activity and expression of iNOS in medulla and cNOS-dependent eNOS in cortex were demonstrated. A role of cNOS in modulating GFR and interstitial fibrosis can be suggested. Prolonged UPJ obstruction would lead to a worsened prognosis on renal injury.